2017
DOI: 10.1101/172759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tolerance to hypothermic and antinoceptive effects of Δ9-tetrahydrocannabinol (THC) vapor inhalation in rats

Abstract: Background and Purpose: Tolerance to the effects of ∆

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Analysis of each treatment day revealed that AM11101 increased 1‐hr food intake on five of 7 days, whereas THC's orexigenic effect was limited to 2 days. While previous studies have shown that THC's behavioural and physiological effects can dissipate in as few as four daily injections (Jarbe & DiPatrizio, ; Nguyen et al, ), we saw no evidence of tolerance to the orexigenic effects of THC or AM11101 in our study. Both compounds increased average 1‐hr food intake across the 7 days, and daily 1‐hr intakes showed no decline from day 1 to day 7.…”
Section: Discussioncontrasting
confidence: 86%
“…Analysis of each treatment day revealed that AM11101 increased 1‐hr food intake on five of 7 days, whereas THC's orexigenic effect was limited to 2 days. While previous studies have shown that THC's behavioural and physiological effects can dissipate in as few as four daily injections (Jarbe & DiPatrizio, ; Nguyen et al, ), we saw no evidence of tolerance to the orexigenic effects of THC or AM11101 in our study. Both compounds increased average 1‐hr food intake across the 7 days, and daily 1‐hr intakes showed no decline from day 1 to day 7.…”
Section: Discussioncontrasting
confidence: 86%
“…Blood samples were collected (~500 ul) via jugular needle insertion under anesthesia with an isoflurane/oxygen vapor mixture (isoflurane 5% induction, 1-3% maintenance) 35 minutes post-initiation of vapor inhalation. Plasma THC content was quantified using fast liquid chromatography/mass spectrometry (LC/MS) adapted from (Irimia et al, 2015; Lacroix and Saussereau, 2012; Nguyen et al, 2017). 5 μL of plasma were mixed with 50 μL of deuterated internal standard (100 ng/mL CBD-d3 and THC-d3; Cerilliant), and cannabinoids were extracted into 300 μL acetonitrile and 600 μL of chloroform and then dried.…”
Section: Methodsmentioning
confidence: 99%
“…The authors are grateful to Shawn M. Aarde for significant contributions to the invention and initial validation of the vapor inhalation method and to Mr. Howard Britton for prototyping inhalation equipment. An earlier version of this manuscript was posted in pre-print form (Nguyen et al, 2017). This is manuscript #29555 from The Scripps Research Institute.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The Protank 3 Atomizer (Shenzhen Kanger Technology Co., LTD; Fuyong Town, Shenzhen, China) with MT32 coil operating at 2.2 Ω is the most common first-generation mod used for preclinical research (Nguyen et al , 2016; Nguyen et al , 2018; Javadi-Paydar et al , 2018; Nguyen et al , 2020; Javadi-Paydar et al , 2019b; Freels et al ., 2020). Later studies used second-generation ENDS systems, which include sub-ohm tanks, such as the SMOK Tank Baby Beast TFV8 with an 0.2 Ω M2 atomizer (SMOKTech, Nanshan, Shenzhen, China) or Herakles Sub Ohm Tank e-cigarette cartridges (Sense; Shenzhen Sense Technology Co., LTD; Baoan Dist, Shenzhen, Guangdong, China) (Nguyen et al , 2018; Nguyen et al , 2019; 2020 Freels et al , 2020). Second-generation ENDS are more efficient, so in order to match the vapor delivered from first-generation systems, second-generation protocols typically utilized a lower frequency or duration of puffs to deliver the same volume of drug vapor.…”
Section: Introductionmentioning
confidence: 99%
“…At the highest concentrations tested (100–200 mg/mL; 30–40 min exposure), temperatures decreased roughly 2–3°C, which is comparable to hypothermic effects seen after an intraperitoneal injection of 20 mg/kg of THC (Nguyen et al , 2016; Javadi-Paydar et al , 2018). In male and female rats, peak hypothermic effects occur at 30–60 min post-vapor initiation and are back to control levels after 4 h (Nguyen et al , 2018; Javadi-Paydar et al , 2018; Nguyen et al , 2020). Tolerance to the hypothermic response to THC vapor emerges after chronic dosing (2–3x daily sessions for >4 days), with evidence that tolerance occurs more quickly in female rats (Nguyen et al , 2018).…”
Section: Introductionmentioning
confidence: 99%